Unmasking Indonesian Neo-Orientalism in Kipandjikusmin’s Langit Makin Mendung - Dwi Rezki Hardianto Putra Rustan; Wahyu Gandi G; Hanita Hanim Ismail (UIN Syarif Hidayatullah Jakarta, 2026)
This research aims to unveil colonial discourses in the Langit Makin Mendung (LMM) works. To achieve this, it employs Orientalism concept and incorporates Critical Discourse Analysis (CDA), initially using the deconstruction method. Through the concept and methods, colonial ambivalence is revealed through the perspective of God, Muhammad, Gabriel, and his family in narrating the boundary between heaven and earth. Heaven as a place of wealth and intelligence, while earth is portrayed as a place of laziness, ignorance, and moral decay. This dichotomy reflects colonial attitudes, positioning heaven as the superior colonial space and earth as the inferior colonized space. The story's ironic elements highlight the undecidability and delayed meaning in the identity of earth's inhabitants. By deconstructing these binary oppositions, the study reveals the persistent influence of colonial discourse in shaping Indonesian literature and society. Additionally, the findings reveal neo-orientalism symptom, where colonial identities and perspectives continue to adapt and re-emerge in new forms, reinforcing dominance through subtler and more covert mechanisms. Ultimately, this study contributing to the field by expanding orientalism concept to Indonesian literature and highlighting the persistence of colonial discourses within postcolonial narratives, filling a critical gap in the understanding of neo-orientalism beyond Western or Middle Eastern contexts.